2005
DOI: 10.1002/hipo.20055
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hippocampal protein synthesis following recall disrupts expression of episodic-like memory in trace conditioning

Abstract: Transition of short-term to long-term memory is referred to as consolidation and the process is dependent on protein synthesis. Recently, several studies have shown that expression of consolidated memory for simple forms of learning tasks (e.g., delay conditioning, contextual fear, inhibitory avoidance) becomes vulnerable to disruption by inhibition of protein synthesis when administered shortly after recall. In the present study, we address whether recall-induced dependence on protein synthesis is a fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 25 publications
(35 reference statements)
3
28
0
Order By: Relevance
“…As reconsolidation, extinction is also initiated by nonreinforced retrieval, and it is expressed as a reduction in the probability of emission of a previously learned response. However, extinction is currently understood as an active learning process (Quirk, 2002;Susuki et al, 2004;Bouton et al, 2006;Myers and Davis, 2007), an hypothesis supported by several reports indicating the dependence of extinction on NMDA and AMPA receptors (Falls et al, 1992;Baker and Azorlosa, 1996;Mead et al, 1999;Walker and Davis, 2002;Mao et al, 2006;Burgos-Robles et al, 2007;Zushida et al, 2007), protein synthesis (Santini et al, 2004;Cammarota et al, 2005b;Runyan and Dash, 2005;Akirav et al, 2006;Berger-Sweeney et al, 2006;Bevilaqua et al, 2006), and gene expression (Cammarota et al, 2003;Herry and Mons, 2004;Lattal et al, 2006;Bredy et al, 2007) in different areas of the brain. Taking this into account, it is hard to envisage how mRNA synthesis inhibitors could possibly enhance a process that, if something, they should be expected to block.…”
Section: Discussionmentioning
confidence: 95%
“…As reconsolidation, extinction is also initiated by nonreinforced retrieval, and it is expressed as a reduction in the probability of emission of a previously learned response. However, extinction is currently understood as an active learning process (Quirk, 2002;Susuki et al, 2004;Bouton et al, 2006;Myers and Davis, 2007), an hypothesis supported by several reports indicating the dependence of extinction on NMDA and AMPA receptors (Falls et al, 1992;Baker and Azorlosa, 1996;Mead et al, 1999;Walker and Davis, 2002;Mao et al, 2006;Burgos-Robles et al, 2007;Zushida et al, 2007), protein synthesis (Santini et al, 2004;Cammarota et al, 2005b;Runyan and Dash, 2005;Akirav et al, 2006;Berger-Sweeney et al, 2006;Bevilaqua et al, 2006), and gene expression (Cammarota et al, 2003;Herry and Mons, 2004;Lattal et al, 2006;Bredy et al, 2007) in different areas of the brain. Taking this into account, it is hard to envisage how mRNA synthesis inhibitors could possibly enhance a process that, if something, they should be expected to block.…”
Section: Discussionmentioning
confidence: 95%
“…In a retrograde amnesia paradigm after concussion brain injury, specific cognitive deficits in retrieval, rather than memory consolidation or storage, have been demonstrated [89], which may or may not resemble anterograde cognitive dysfunction. The inclusion of protein synthesis inhibitors before, during and after training could further elucidate the nature of the hippocampaldependent consolidation deficit [49,50,74]. In the amygdala, the absence of neuronal loss substantiates the absence of an amygdala-dependent cognitive deficit, leaving the conditioned context deficit likely to result from functional alterations in remaining injured hippocampal neurons [88].…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that when re-exposure duration is held constant, weaker memories (i.e., those trained with relatively few trials) tend to be enhanced with postreactivation ANI, suggesting an extinction disruption; whereas stronger memories tend to be impaired with postreactivation ANI, suggesting a reconsolidation disruption (but see Suzuki et al, 168 Eisenberg et al 322 and Runyan and Dash 325 ).…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%